Rosemary Gladstar's medicinal herbs : a beginner's guide - Gladstar, Rosemary (Storey Pub., 2012)
Rosemary Gladstar offers an introduction for a new generation of gardeners and natural health and self-sufficiency enthusiasts. Thirty-three of the most common and versatile healing plants are profiled in depth to get the budding herbalist off on the right foot. Readers will learn how to grow, harvest, prepare, and use each herb. Step-by-step instructions explain how to prepare herbal teas, salves, syrups, tinctures, oils, and liniments to stock the home medicine chest. Simple recipes explore each plant's healing qualities -- aloe lotion for poison ivy, dandelion-burdock tincture for sluggish digestion, and lavender-lemon balm tea for stress relief.